Multifocal Independent Spike Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The relationship of the syndrome of multifocal independent spikes (MIS) to hypsarrhythmia and the slow spike-wave (Lennox-Gastaut) syndrome was studied in 64 children with MIS examined during a 3-year period at the Cleveland Clinic, Ohio.